QoS in 4G scenarios using NSIS protocol - Ferreira, Fábio (2012)
This paper presents qualaty of service mechanisms, based on NSIS ( Next Steps in Signaling) protocol. For that, it was implemented a testbed with NSIS running through IPv6. The network's QoS was mesured by the number of drops, for each flow (either QoS or Best Effort traffic), occurred inrouters. The first experiment shows the captured packets during a node association and request for QoS, namely a GIST session and a QoS NSLP session. The second experiment illustrates a more realistic scenario and Best Effort traffic, were simultaneously sent through a path accross diferent networks. The experimental study addressed in this work helped on the enhancement of NSIS developments for IPv6 environments.